2021
DOI: 10.7717/peerj.11962
|View full text |Cite
|
Sign up to set email alerts
|

Plastic response of Medicago sativa L. root system traits and cold resistance to simulated rainfall events

Abstract: Climate change (rainfall events and global warming) affects the survival of alfalfa (Medicago sativa L.) in winter. Appropriate water management can quickly reduce the mortality of alfalfa during winter. To determine how changes in water affect the cold resistance of alfalfa, we explored the root system traits under different rainfall events and the effects on cold resistance in three alfalfa cultivars. These were exposed to three simulated rainfall events (SRE) × two phases in a randomized complete block desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 78 publications
(131 reference statements)
4
8
0
Order By: Relevance
“…Li et al ( 2020 ) argued that root systems shifted from a herringbone branching pattern to a dichotomous branching pattern when plants adjust to drought stress. More recently, Li et al ( 2021 ) also showed that a dichotomous branching pattern is beneficial to cold resistance. Yet, work by Hao et al ( 2021 ) failed to find soil texture influencing the topological index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al ( 2020 ) argued that root systems shifted from a herringbone branching pattern to a dichotomous branching pattern when plants adjust to drought stress. More recently, Li et al ( 2021 ) also showed that a dichotomous branching pattern is beneficial to cold resistance. Yet, work by Hao et al ( 2021 ) failed to find soil texture influencing the topological index.…”
Section: Discussionmentioning
confidence: 99%
“…The TI indirectly describes the uptake efficiency of roots for water and nutrients, for which Fitter ( 1994 ) proposed two extreme branching patterns, namely, the dichotomous branching pattern ( TI = 1) to adapt to nutrient-poor soils and the herringbone branching pattern for the nutrient-rich soils ( TI = 0.5). However, due to the influences from plant growth characteristics, soil fertilities, and soil compaction, the TI values always range from 0.5 to 1 (Fitter, 1994 ; Magalhães and Seifert, 2015 ; Li et al, 2020 , 2021 ; Hao et al, 2021 ). In our study, the root system of C. funebris branching pattern changed from a herringbone branching pattern (having a small number of internal links, many external links, many secondary branches, and internal overlaps) to a dichotomous branching pattern exhibiting more internal links, fewer external links, fewer secondary branches, less overlap, and weaker internal competition ( Figures 3A–C ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the root productivity in June of the planting year was significantly correlated with ANPP in both the current and following year (Table 4). Rapid growth of the root system in the early stages of plant growth is essential for alfalfa productivity, but further research is required to explore the specific mechanisms and processes involved [33].…”
Section: Fertilizer Increases Alfalfa Productivity In Saline Soilmentioning
confidence: 99%
“…In northern China, because of the extended periods of sub-zero air and soil temperatures, only cold tolerant cultivars can be grown. These cultivars can tolerate extremely low temperatures during winter, but they can also adapt to temperature fluctuations in spring 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%